Cassava cultivation and soil productivity - Howeler, Reinhardt H. (Burleigh Dodds Science Publishing Limited, 2017)
Cassava is becoming an ever more important crop, and over the past 20–30 years its planted area has increased faster than that of any other food crop. However, yields are still low due to the fact that the crop is usually grown on infertile soils and without adequate soil and crop management. This chapter begins by discussing nutrient absorption, distribution within the plant, and removal by the cassava harvest. Section 3 then considers the effect of cassava cultivation on soil productivity. Section 4 reviews the nutrient loss in eroded sediments and runoff in soils used for cassava cultivation. Finally, Section 5 discusses how cassava farmers can diagnose nutritional problems in their crop.